ANALISIS PENGARUH TINGKAT LITERASI KEUANGAN, KECERDASAN SPIRITUAL DAN EKONOMI ORANG TUA TERHADAP PENGELOLAAN KEUANGAN MAHASISWA: (Studi Kasus Pada Mahasiswa Fakultas Ekonomi Angkatan 2019 Tahun 2021-2022 (Genap) Universitas Mahaputra Muhammad Yamin Solok) - Nuzul Raudhatul Sudirsa; Wahyu Indah Mursalini; Ida Nirwana (Student Research Journal, 2023)
This research was conducted at Mahaputra Muhammad Yamin University, Solok. The purpose of this study was to determine the effect of financial literacy, spiritual intelligence and people's economy on the financial management of students at the Ummy Solok Faculty of Economics. From the population, 75 respondents were taken as samples. The data collection method used is library and field (questionnaire). Based on multiple linear regression analysis of the variables of financial literacy, spiritual intelligence and parents' economics on student financial management in the student study of the Faculty of Economics Ummy Solok Y= 12,862 + 0,213X1 + 0,382X2 + 0,034X3 + e. From the t-test carried out on the financial literacy variable X1 the t count value of 1.599 < t table (1.66629) and the significance value of 0.114 > 0.05, it can be concluded that the financial literacy variable (X1) is rejected, which means that there is no effect of X1 on Y. Variable X2 spiritual intelligence t count 3.253 < t table (1.66629) and the significance value is 0.002 <0.05, it can be concluded that the spiritual intelligence variable (X2) is accepted, which means that there is an effect of X2 on Y. t table (1.66629) and the significance value is 0.536 > 0.05, it can be concluded that the economic variable of parents (X3) is rejected, which means that there is no effect of X3 on Y. From the f test conducted that financial literacy, spiritual intelligence and Parent's economy has a simultaneous effect on student financial management fcount 11.034 > f table 2.73 with a significance value of 0.000 < 0.05. From the results of the analysis of the coefficient of determination obtained R Square of 0.289 or 28.9%. This indicates that the contribution of parents' financial literacy, spiritual intelligence, and economic variables is 28.9% and 71.1% is influenced by other variables.